CARTOGRAPHY AND VISUAL CORRESPONDENCES THOUGHT AND REALITY OF MODERNISM IN EUROPE AND CHINA - Michela BONATO (European Journal of Geography)
With the coming of the second industrial revolution in England, great changes took place also within the European society, in particular a new concept of urban planning, and an early form of soil gentrification came to light. The middle class had finally won a place in politics, while academics invited the governments to review the entire landscape of human relationships through the eye of Modernism. Europe then engaged in a civilizing mission, transplanting factories and thoughts worldwide. Considering the modernist movement from a transcultural perspective we thus aim to analyze the development and implementation of the theories into the practice, as to underline the differences and convergences among some places on a global level. We look in particular at Europe and China as a flourishing urban milieu, with the Chinese city of Chongqing as basis to study the turning points between ancient and modern society in China, and Paris in France as the place in which the ideas of urbanization, social regulation, and sanitation have come into being in their very first stage. We focus our discourse on the divergence between cartography and reality, putting emphasis on the concept of visual utopia. Through the analysis of some Chongqing old maps it will be finally possible to appreciate the Chinese peculiar cartographic methods, and the subsequent assimilation of the European ‘scientific’ methods of cartographic survey in China.